Effects of a Multi-Ingredient Preworkout Supplement Versus Caffeine on Energy Expenditure and Feelings of Fatigue during Low-Intensity Treadmill Exercise in College-Aged Males - Daniel J. Lutsch; Clayton L. Camic; Andrew R. Jagim; Riley R. Stefan; Brandon J. Cox; Rachel N. Tauber; Shaine E. Henert (MDPI AG, 2020)
The primary purpose of this study was to examine the acute effects of a multi-ingredient (i.e., caffeine, green tea extract, Yohimbe extract, capsicum annum, coleus extract, L-carnitine, beta-alanine, tyrosine) preworkout supplement versus a dose of caffeine (6 mg·kg−1) on energy expenditure during low-intensity exercise. The effects of these treatments on substrate utilization, gas exchange, and psychological factors were also investigated. Twelve males (mean ± SD: age = 22.8 ± 2.4 years) completed three bouts of 60 min of treadmill exercise on separate days after consuming a preworkout supplement, 6 mg·kg−1 of caffeine, or placebo in a randomized fashion. The preworkout and caffeine supplements resulted in significantly greater energy expenditure (p < 0.001, p = 0.006, respectively), <semantics><mover>V˙</mover>O</semantics>2 (p < 0.001, p = 0.007, respectively), <semantics><mover>V˙</mover></semantics>CO2 (p = 0.006, p = 0.049, respectively), and <semantics><mover>V˙</mover></semantics>E (p < 0.001, p = 0.007, respectively) compared to placebo (collapsed across condition). There were no differences among conditions, however, for rates of fat or carbohydrate oxidation or respiratory exchange ratio. In addition, the preworkout supplement increased feelings of alertness (p = 0.015) and focus (p = 0.005) 30-min postingestion and decreased feelings of fatigue (p = 0.014) during exercise compared to placebo. Thus, the preworkout supplement increased energy expenditure and measures of gas exchange to the same extent as 6 mg·kg−1 of caffeine with concomitant increased feelings of alertness and focus and decreased feelings of fatigue.